Combination of 4-1BB and DAP10 promotes proliferation and persistence of NKG2D(bbz) CAR-T cells - Wei, Cheng; Xia, Kangfu; Xie, Yucheng; Ye, Sishi; Ding, Yanghui; Liu, Zairu; Zheng, Rong; Long, Jing; Wei, Qinchuan; Li, Yumei; Yang, Dongxia; Xu, Xiaojun; et al. (Frontiers in Oncology, 2022)
Chimeric antigen receptor (CAR)-T cell therapy has been shown to have considerable therapeutic effects in hematological malignancies, and NKG2D(z) CAR-T cell therapy has been verified to be safe based on clinical trials. However, due to the poor persistence of NKG2D(z) CAR-T cells, their therapeutic effect is not obvious. Here, we constructed NKG2D(bbz) CAR-T cells that can simultaneously activate 4-1BB and DAP10 costimulatory signaling. They were found to be cytotoxic to the target cells in vitro and in vivo. They exhibited low differentiation, low exhaustion, and good proliferation. Importantly, the proportions of central memory T (Tcm) and stem cell-like memory T (Tscm) cell subsets were strikingly increased. After long-term incubation with the target cells, they displayed reduced exhaustion compared to NKG2D(z) CAR-T cells. Further, in the presence of the phosphoinositide 3-kinase (PI3K) inhibitor LY294002, they exhibited reduced exhaustion and apoptosis, upregulated Bcl2 expression, and an increased proportion of Tcm cell subsets. Finally, NKG2D(bbz) CAR-T cells had better antitumor effects in vivo. In summary, the results showed that NKG2D(bbz) CAR-T cells may be valuable for cellular immunotherapy of cancer.